Long-term dynamics of Norovirus transmission in Japan, 2005–2019 - Misumi, Megumi; Nishiura, Hiroshi (PeerJ, 2021)
Norovirus continues to evolve, adjusting its pathogenesis and transmissibility. In the present study, we systematically collected datasets on Norovirus outbreaks in Japan from 2005 to 2019 and analyzed time-dependent changes in the asymptomatic ratio, the probability of virus detection, and the probability of infection given exposure. Reports of 1,728 outbreaks were published, and feces from all involved individuals, including those with asymptomatic infection, were tested for virus in 434 outbreaks. We found that the outbreak size did not markedly change over this period, but the variance in outbreak size increased during the winter (November–April). Assuming that natural history parameters did not vary over time, the asymptomatic ratio, the probability of virus detection, and the probability of infection given exposure were estimated to be 18.6%, 63.3% and 84.5%, respectively. However, a model with time-varying natural history parameters yielded better goodness-of-fit and suggested that the asymptomatic ratio varied by year. The asymptomatic ratio was as high as 25.8% for outbreaks caused by genotype GII.4 noroviruses. We conclude that Norovirus transmissibility has not changed markedly since 2005, and that yearly variation in the asymptomatic ratio could potentially be explained by the circulating dominant genotype.
Keywords: Caliciviridae; Natural history; Transmission; Asymptomatic ratio; Epidemiology; Epidemic